PENGARUH KOMPENSASI DAN PELATIHAN TERHADAP KINERJA PEGAWAI - AMIRULLAH; AWIK KHOLIDAH (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2019)
This study aims to analyze and explain the Effect of Compensation and Training on Employee Performance. This research was conducted using a survey method for employees at the UB's Faculty of Agriculture Malang with a total sample of 56 respondents. The analytical tool used is multiple linear regression analysis. The results showed that compensation and training simultaneously had a significant effect on employee performance. Compensation and Training partially have a significant effect on employee performance. Partially, the compensation variable has a dominant effect on employee performance.